Medical language for modern health care - Allan, David M. (McGrawHill, 2008)
Combining the Time-Tested A & P Approach with a New Contextual Approach, MEDICAL LANGUAGE FOR MODERN HEALTH CARE Promotes Active Learning Chapters in the textbook are organized by body system in accordance with an overall anatomy and physiology (A & P) approach. Lessons introduce and define terminology through the context of A & P, pathology, and clinical and diagnostic procedures/tests. The organization of the body systems into chapters is based on an “outside to inside” sequence that reflects a physician’s differential diagnosis method used during an examination. To provide students with an authentic context, the medical specialty associated with each body area or system is introduced along with the anatomy and physiology. Students actually step into the role of an allied health professional associated with each specialty. Patient cases and documentation are used to illustrate the real-life application of medical terminology in modern health care: to care for and communicating with patients, and to interact with other members of the health care team. The A & P organizational approach, used in conjunction an authentic medical setting and patient cases, encourages student motivation and facilitates active, engaged learning. Each chapter is structured around a consistent and unique framework of pedagogic devices. No matter what the subject matter of a chapter, the structure enables students to develop a consistent learning strategy, making Medical Language for Modern Health Care a superior learning tool.